The role of multimodality imaging in diabetic cardiomyopathy: a brief review - Adel, Fadi W.; Chen, Horng H. (Frontiers in Endocrinology, 2024)
Diabetic cardiomyopathy (DMCM), defined as left ventricular dysfunction in the setting of diabetes mellitus without hypertension, coronary artery disease or valvular heart disease, is a well-recognized entity whose prevalence is certainly predicted to increase alongside the rising incidence and prevalence of diabetes mellitus. The pathophysiology of DMCM stems from hyperglycemia and insulin resistance, resulting in oxidative stress, inflammation, cardiomyocyte death, and fibrosis. These perturbations lead to left ventricular hypertrophy with associated impaired relaxation early in the course of the disease, and eventually culminating in combined systolic and diastolic heart failure. Echocardiography, cardiac nuclear imaging, and cardiac magnetic resonance imaging are crucial in the diagnosis and management of the structural and functional changes associated with DMCM. There appears to be a U-shaped relationship between glycemic control and mortality. Exogenous insulin therapy, while crucial, has been identified as an independent risk factor for worsening cardiovascular outcomes. On the other hand, Glucagon-like Peptide-1 Receptor Agonists and Sodium–Glucose Cotransporter 2 Inhibitors appear to potentially offer glycemic control and cardiovascular protection. In this review, we briefly discuss the pathophysiology, staging, role of multimodality imaging, and therapeutics in DMCM.